Digital readiness and financial inclusion: Determinants of MSMEs adoption of digital gold pawn services - Rio Laksamana; Isna Ayulestari (Environmental, Social, Governance and Sustainable Business, 2025)
Background: Financial service digitalization has emerged as a strategic mechanism for expanding financial inclusion, particularly among Micro, Small, and Medium Enterprises (MSMEs) facing persistent barriers to formal financing. Pegadaian, as Indonesia's state-owned pawnshop institution, has developed digital gold pawn services to enhance accessibility; however, successful adoption depends critically on MSME readiness and behavioral intentions. Methods: This study employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data collected from 120 MSMEs actors in Pontianak City through purposive sampling. The research examines the influence of financial literacy, digital readiness, perceived ease of use, perceived security, and trust on adoption intention. Findings: Results reveal that digital readiness (β=0.412, p<0.001) emerges as the most dominant determinant of adoption intention, followed by financial literacy (β=0.287, p<0.01), perceived ease of use (β=0.245, p<0.01), perceived security (β=0.198, p<0.05), and trust in Pegadaian (β=0.176, p<0.05). The model explains 68.3% of the variance in adoption intention (R²=0.683). Conclusion: Pegadaian's digital gold pawn services demonstrate substantial potential for broadening MSME financial inclusion, particularly for non-bankable enterprises with gold collateral. Success requires user-oriented digitalization strategies, enhanced financial literacy programs, simplified service processes, and strengthened institutional trust and security mechanisms. Novelty/Originality of this article: This study uniquely examines MSME readiness for digital pawn services in a regional Indonesian context, extending digital adoption frameworks to asset-based financing and contributing to understanding financial inclusion pathways for non-bankable MSMEs.